The expression

$\tan\theta+2\tan(2\theta)+2^2\tan(2^2\theta)+\dots+2^{14}\tan(2^{14}\theta)+2^{15}\cot(2^{15}\theta)$ equals to :

The answer in the answer book is given to be $\cot\theta$. I am unable to think in which way to proceed to find the required solution.

thanks in advance!

  • 3
    $\begingroup$ Look at $\tan x + 2 \cot (2x)$, and see whether you get something telescoping. $\endgroup$ – Daniel Fischer May 2 '15 at 9:41


$$a\tan\beta+2a\cot(2\beta)=a\left(\tan\beta+2\cdot\frac{1-\tan^2\beta}{2\tan\beta}\right)=a\cot\beta.$$ So, one has $$2^{14}\tan(2^{14}\theta)+2^{15}\cot(2^{15}\theta)=2^{14}\cot(2^{14}\theta)$$ $$2^{13}\tan(2^{13}\theta)+2^{14}\cot(2^{14}\theta)=2^{13}\cot(2^{13}\theta)$$

and so on.


$$\cot x-\tan x=\dfrac{\cos^2x-\sin^2x}{\sin x\cos x}=2\cot2x$$

Set $x=\theta,2\theta,2^2\theta,\cdots.2^n\theta$ where $n$ is a non-negative integer

$$\cot\theta-\tan\theta=2\cot2\theta\ \ \ \ (1)$$

$$2(\cot2\theta-\tan2\theta)=2(2\cot2^2\theta)\ \ \ \ (2)$$

$$2^2(\cot2^2\theta-\tan2^2\theta)=2^2(2\cot2^3\theta)\ \ \ \ (3)$$


$$2^n(\cot2^n\theta-\tan2^n\theta)=2^n(2\cot2^{n+1}\theta)\ \ \ \ (n)$$

Adding we get $$\displaystyle\cot\theta-\sum_{r=1}^n2^r\tan2^r\theta=2^{n+1}\cot2^{n+1}\theta$$



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.